2015
DOI: 10.12659/msm.892898
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of the Association between Plasminogen Activator Inhibitor-1 4G/5G Polymorphism and Recurrent Pregnancy Loss

Abstract: BackgroundThe association between plasminogen activator inhibitor-1 (PAI-1) 4G/5G polymorphism and recurrent pregnancy loss (RPL) risk is still contradictory. We thus performed a meta-analysis.Material/MethodsRelevant studies were searched for in PubMed, Web of Science, Embase, and Cochrane Library. An odds ratio (OR) with a 95% confidence interval (CI) was used to assess the association between PAI-1 4G/5G polymorphism and RPL risk.ResultsA total of 22 studies with 4306 cases and 3076 controls were included i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 33 publications
2
31
1
2
Order By: Relevance
“…Previous studies have found an association between PAI‐1 ‐675 4G/5G polymorphism and RPL and to a lesser extent, RIF . In this study, we aim to investigate the association between PAI‐1 4G/5G polymorphism with various types of reproductive failures and compare the metabolic, hormonal, and immune profiles of these patients in association with PAI‐1 genotypes.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies have found an association between PAI‐1 ‐675 4G/5G polymorphism and RPL and to a lesser extent, RIF . In this study, we aim to investigate the association between PAI‐1 4G/5G polymorphism with various types of reproductive failures and compare the metabolic, hormonal, and immune profiles of these patients in association with PAI‐1 genotypes.…”
Section: Introductionmentioning
confidence: 97%
“…Several polymorphisms within the PAI‐1 gene have been reported to influence PAI‐1 level. One of the most common PAI‐1 gene polymorphisms is ‐675 4G/5G insertion–deletion mutation, and this polymorphism has been associated with polycystic ovary syndrome (PCOS), diabetes mellitus, thromboembolism, pre‐eclampsia, asthma, recurrent pregnancy losses (RPL), endometrial cancer, breast cancer, and coronary heart diseases …”
Section: Introductionmentioning
confidence: 99%
“…Our results are similar to the results of a meta-analysis by Chen et al [16] which confirmed that PAI-1 4G/5G polymorphisms play a potential role in SMs, indicating that the PAI-1 4G/5G polymorphism is significantly associated with a risk of SM (OR = 1.70, 95% CI 1.21-2.38). Results of another meta-analysis conducted by Xuejiao et al [17] suggest that the PAI-1 4G/5G polymorphism might be associated with SM development specifically in Caucasians (OR = 2.23, 95% CI 1.44-3.46). Previously, Glueck et al [18] stated that homozygosity for the 4G allele of the PAI-1 gene represents a serious risk for pregnancies, predisposing to prematurity, intrauterine growth retardation, miscarriage, and stillbirth.…”
Section: Discussionmentioning
confidence: 99%
“…When it comes to CVT, according to our knowledge so far only one type has been carried out of observational study "case-control", which has not shown that allelic variant of 4G/5G PAI-1 gene significantly affects the risk of this disorder, unlike mutations of prothrombin G20210A (22). *** Additionally, the PAI-1 4G/5G polymorphism was associated with the risk of the numerous and varied other clinical disorders such as diabetic mellitus and its chronic complications (23,24), recurrent miscarriage (25), preeclampsia (26), polycystic ovary syndrome (27), bronchial asthma (28), cancer (especially colon and endometrium) (29), sepsis (including fatal outcome as a result) (30) etc, where due to unreconciled opinions, further studies on this are carried out intensively.…”
Section: Discussionmentioning
confidence: 99%